Optimising the quality of antibiotic prescribing in out-of-hours primary care in Belgium: a study protocol for an action research project. Issue 10 (15th October 2017) - Colliers, Annelies; Coenen, Samuel; Philips, Hilde; Remmen, Roy; Anthierens, Sibyl
Abstract : Introduction: Antimicrobial resistance is a major public health threat driven by inappropriate antibiotic use, mainly in general practice and for respiratory tract infections. In Belgium, the quality of general practitioners' (GPs) antibiotic prescribing is low. To improve antibiotic use, we need a better understanding of this quality problem and corresponding interventions. A general practitioners cooperative (GPC) for out-of-hours (OOH) care presents a unique opportunity to reach a large group of GPs and work on quality improvement. Participatory action research (PAR) is a bottom-up approach that focuses on implementing change into daily practice and has the potential to empower practitioners to produce their own solutions to optimise their antibiotic prescribing. Methods: This PAR study to improve antibiotic prescribing quality in OOH care uses a mixed methods approach. In a first exploratory phase, we will develop a partnership with a GPC and map the existing barriers and opportunities. In a second phase, we will focus on facilitating change and implementing interventions through PDSA (Plan-Do-Study-Act) cycles. In a third phase, antibiotic prescribing quality outside and antibiotic use during office hours will be evaluated. Equally important are the process evaluation and theory building on improving antibiotic prescribing. Ethics: The study protocol was approved by the Ethics Committee of the Antwerp University Hospital/University of Antwerp. PAR unfolds in response to the needs and issues of the stakeholders, therefore new ethics approval will be obtained at each new stage of the research. Dissemination: Interventions to improve antibiotic prescribing are needed now more than ever and outcomes will be highly relevant for GPCs, GPs in daily practice, national policymakers and the international scientific community. Trial registration number: NCT03082521 ; Pre-results.